Nomenclatural itch versus patrolling itch: comments on O’Hara (2011) - Nemésio, André (Zootaxa, 2011)
In the last years there have been renewed criticisms towards those who, theoretically, abuse of naming new taxa, supposedly with the only (or main) objective of having their names associated to the nomina of these taxa and, thus, being ‘immortalized’ (Pillon & Chase 2007[1]; Dubois 2008; Evenhuis 2008). As Evenhuis (2008) has carefully shown, however, this kind of criticism is almost as old as taxonomy itself and those erecting supposedly unnecessary nomina are often considered to be suffering the mihi itch (‘mihi’ is the Latin for ‘to me’, alluding to an egotistical affliction). In fact, even Linnaeus has been later indirectly accused of being afflicted by the mihi itch: “It has often been pointed out that Linnaeus had no idea of a principle of priority. Indeed, he was in no moral position to hold any such idea, engaged as he was in rejecting nearly all existing names of species” (Melville 1995: 5) and, of course, giving them nomina of his own.